Metabesity: The sword with two edges - Muhammad Kashif Shaikh, Syed Zulfiquar Ali Shah, Imran Karim, Shagufta Laila Memon, Shafaq Jabeen, Samar Raza (Pakistan Journal of Medical & Health Sciences, 2024)
Pakistan is positioned among the top ten countries in terms of the prevalence of obesity, which exposes its citizens to a heightened risk of developing metabolic disorders and metabolic conditions. Metabolic disorders, such as diabetes, manifest concurrently with obesity and other metabolic disorders. Weight gain is additionally correlated with cardiovascular and neurovascular diseases, as well as accelerated ageing, in addition to the aforementioned complications1. Metabolic conditions are distinguished by an intricate interplay of genetic, behavioural, and metabolic elements; thus, comprehensive management protocols are especially crucial, especially for the population of Pakistan. For this purpose, standardized guidelines and literature that had undergone rigorous evaluation were consulted, including those established by the American Society of Clinical Endocrinology (AACE). Regular examinations for diabetes, dyslipidemia, and cardiovascular diseases, a uniform set of diagnostic criteria, are advised by established protocols for the management of metabesity. Risk assessment involves the evaluation of several physiological parameters, including fasting blood sugar levels (>99mg/dL), high blood pressure (>135/85mmHg), and waist circumference (>90cm in men and >80cm in women in accordance with Asian-based guidelines). The lipid profile (HDL <40mg/dl in men and <50mg/dl in women) is also assessed2,3.